Antecedent, Consequence and Moderator Factors of Work-Family Conflict Among Woman Academicians in Yogyakarta, Indonesia - Hardyastuti, Suhatmini (2000)
Married working women play multiple roles as Wives, mothers, homemakers and employees, simultaneously. However, employers tend to view employees' problems related to work and family roles separately. These conditions result in work-family conflict as working women try to balance the demands of work and family roles. This study was conducted to determine the extent of work-family conflict experienced by married working women, and to examine factors that relate and contribute to work-family conflict as well as consequences of the conflict on women' s well-being. The interaction effect of moderator factors on the relationships between work-family conflict and women's well-being were also studied. Using self-administered questionnaires, data were obtained from 267 woman academicians from two state universities in Yogyakarta, Indonesia. This study found that the married working women experienced varying intensities of work-family conflict due to their multiple roles. This finding is consistent with the role theory which postulates that the expectations of work role can generate interrole conflict when they involve pressures to dominate the time of focal person and interfere with fulfilling the expectations of family role, or vice versa.